TASAWUF DAN PEMBANGUNAN ROHANI DIKALANGAN MASYARAKAT - Muhammad Khairi Mahyuddin; Roslee Ahmad; Atifah Mamat; Awatif Abdul Rahman (Jurnal Ushuluddin Adab dan Dakwah, 2018)
Sufism is a science that is often misunderstood by the general public as passive and setback. There is a negative view of the terminology and meaning of Sufism as a science taken from other religious sources and associated with heresy. The approach of this writing is narrative and descriptive based on reference to Islamic literature. The result of finding that Sufism is a true science originating from the Koran and al-Sunnah and is active and progressive is awakening the community and the state based on the views of the scholars of the scholars of Ahl al-Sunnah wa al-Jama'ah.